Determination of the hydraulic conductivity function of grey Vertosol with soil column test. Issue 11 (November 2020) - Udukumburage, Rajitha Shehan; Gallage, Chaminda; Dawes, Les; Gui, Yilin
Abstract: Expansive soils exhibit swell-shrink behaviour in wet-dry periods resulting in distresses on light-weight structures founded on/in them. Therefore, it is essential to investigate the climate-ground interaction when designing structures on expansive soils. Laboratory-based models are preferred to investigate the climatic-ground interaction of expansive soils due to the uncontrollability of the boundary conditions and expenses associated with field monitoring. More flexibility in analysing the climatic-induced hydraulic responses in expansive soils can be achieved by finite element modelling of data from physical model tests. However, these laboratory-based models regularly encounter the effects of boundary flaw, preferential flow paths and entrapped air that needs to be accounted for when numerically simulated. In this study, the authors aim to numerically model the hydraulic responses in an instrumented Vertosol soil column (ISC) under controlled laboratory conditions. The effects of the preferential flow paths and boundary flaws were incorporated into a modified hydraulic conductivity as a practical approach to model the hydraulic responses in ISC. Influence of the entrapped air was rectified by a suitable correction factor. These findings present a practical method for geotechnical practitioners to accurately estimate the suction and volumetric water content profiles in laboratory-based expansive soil model tests. Abstract : Civil engineering; Earth sciences; Environmental science; Geotechnical engineering; Construction engineering; Soil composition; Soil hydrology; Environmental engineering; Unsaturated soil; Expansive soil; Numerical simulation; Climate-ground interaction; Mechanical properties; Sensors; Wetting